2022
DOI: 10.1186/s12913-022-08112-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the quality and functioning of oncological multidisciplinary team meetings: results of a systematic review

Abstract: Background Discussing patients with cancer in a multidisciplinary team meeting (MDTM) is customary in cancer care worldwide and requires a significant investment in terms of funding and time. Efficient collaboration and communication between healthcare providers in all the specialisms involved is therefore crucial. However, evidence-based criteria that can guarantee high-quality functioning on the part of MDTMs are lacking. In this systematic review, we examine the factors influencing the MDTMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 98 publications
(256 reference statements)
0
23
0
Order By: Relevance
“… 4 21 Most of them require an observer that scores predefined quality items such as attendance of core members and availability of all required patient data. 21 These evaluation tools were thought the be useful in guiding the evaluation process. Whether they actually optimise MDTM functioning is not yet proven and needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 4 21 Most of them require an observer that scores predefined quality items such as attendance of core members and availability of all required patient data. 21 These evaluation tools were thought the be useful in guiding the evaluation process. Whether they actually optimise MDTM functioning is not yet proven and needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, after an extensive literature search we found that there is a lack of a clear definition for a ‘high-quality MDTM’, since ‘quality’ is a subjective concept. 21 Therefore, we focused in our exploratory interview study on factors that reasonably contribute to the execution of an optimal MDTM. This makes our findings less specific and measurable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations